Integrated Automotive Safety Handbook. - Gonter, Mark (SAE International, 2013)
Even though a number of developed countries enjoy a high level of vehicle safety, more than 1.2 million fatalities still occur each year on roadways worldwide. There remains a need to continue improving vehicle and road safety. New technologies in sensors and electronic control units, and the growing knowledge of car-to-car and car-to-infrastructure technologies have led to a fusion of the previously separated areas of accident avoidance (popularly known as active safety) and mitigation of injuries (popularly known as passive safety) into the newer concept of integrated vehicle safety. This ne.